Quantifying the technical diversity of elite tennis players during match play - Zhao, Z.; Cui, Y.; Qi, B. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Winning elite tennis match necessitates the considerable repertoire of technical skills to attune relevant tactics. Previous studies evaluated the impact of specific technical indicators on match outcome such as serve efficiency, ace%, but little research comprehensively assess the level of technical variety players may demonstrate during competitive scenarios. Therefore, the study aimed to model the diversity in technical performance among elite tennis players during matches in relation to gender and match outcome. METHODS: Match performance data of 236 singles matches (136 for male and 130 for female) from the 2023 Australian Open and US open were retrieved from a publicly-accessed match statistics website. In total, 50 male (Ranking of Association of Tennis Professionals: 1 to 82) and 50 female professional players (WTA ranking from 1 to 78) with 532 observations were included. Standard entropies of the following 7 technical performance categories were derived to reflect player`s technical diversity: first/second serve, serve landing area in deuce/advantage courts, forehand\backhand shot direction (down the line, crosscourt, down the middle, inside-out, inside-in) and shot type (flat/topspin, slice, volley, smash, lob, drop shot). The mixed linear model was utilized to analyze the effects of gender and match outcome on each technical diversity. RESULTS: The results indicate that match outcome and gender had no statistically significant interaction effect on all 7 technical performances (p>0.05). But match outcome and gender have showed significant main effects on shot type, forehand/backhand baseline shot direction, first serve area (p<0.05, r-squared conditional=0.17-0.70). Losing players showed higher level of diversity of shot type (ES=0.33, small) than for winning players. Male players generally had higher degrees of diversity in shot type, forehand baseline shot direction (ES=0.63-0.97, moderate) than female players, while lower in backhand baseline shot direction, first serve area (ES=0.62-0.70, moderate). CONCLUSION: The higher diversity of shot types in winning players compared to losing players may be attributed to the necessity of having a reliable scoring technique to secure victory. Accordingly, it is advisable to emphasize on the training of stable scoring techniques.The higher diversity of shot types and forehand baseline shot direction in male compared to female may be attributed to the fact that male generally exhibit more tactical variations in matches by launching forehand attacks more frequently than female. Therefore, elite female players are recommended to incorporate additional tactical training focused on forehand combinations while developing their footwork.The lower diversity of first serve area in male compared to female suggests that males first serves tend to be directed more towards the outer or inner corners. This indicates a high demand for serving precision in elite males matches, emphasizing the need to enhance serving skills in training.